PENDAMPINGAN IBU-IBU MENINGKATKAN PEREKONOMIAN KELUARGA PEMBUATAN SELADA - Amelia, Rizki; Susanti, Emilia; Suhertina, Suhertina; Ibrahim, Nelvia; Noviarni, Noviarni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This Community Service Activity aims to assist mothers in making lettuce in order to improve family economy. This community service activity was carried out in Sidolmulyo Barat Village, Tuah Madani District, Pekanbaru City. The method of this community service activity is carried out by providing assistance and training in making lettuce.. The results of this Community Service Activity show that by introducing and holding training in making traditional food, it can improve the family economy. The lettuce-making mentoring program went well and smoothly. The participants were enthusiastic and planned to develop this knowledge for sales ideas and food businesses to improve the family economy in order to meet daily needs.